An analysis of spectrum allocation for the mobile phone services - Bahar, Tadjadine Hisseine (School of Economics, 2022)
This paper investigates the relationship between the spectrum allocation policy and the mobile broadband cost in 135 countries between 2012 and 2019, with a particular focus on developing countries. We construct a panel data collected from various sources such as World Development Indicator (WDI), International Telecommunication Union (ITU) - ICT Price Baskets (IPB), Global Mobile Frequencies Database of Spectrum Monitoring Technology Advisors databases and other additional sources to conduct our empirical analysis. We estimate a system of equations - demand and supply for mobile broadband services with the following findings. First, demand for mobile Internet is negatively impacted by the price of 1GB of mobile broadband, as suggested by economic theory. Second, GDP per capita has a positive impact on the mobile broadband penetration. In the pricing equation, 79% of overall variation in mobile broadband price is explained by the list of exogenous variables included in our model specification. We find that the mobile broadband price is decreasing with population density which is an indication of economies of scale. Moreover, the price of mobile broadband increases with Herfindahl-Hirschman Index. Also, prices decrease when the market structure changes from monopoly to competition. The price of mobile broadband decreases for a greater volume of radio spectrum available to all the operators within country. Moreover, auction mechanism of spectrum allocation reduces the mobile broadband price. Our results imply that the regulatory authority and policy makers need to promote access of radio spectrum for mobile services. Moreover, a spectrum assignment mechanism based on auctions contributes to the economic efficiency by reducing marginal cost and prices of mobile broadband services.